Amateur Radio station - (Creator); (Contributor) (1958)
Amateur Radio station VE8MA. Note John Gilbert’s old DX 100. The Collins transmitter must have been unserviceable. The DX 100 was purchased by George Butler when John left on April 23, 1958. Personal communications from Isachsen was handled by radio amateurs including VE6HM in Edmonton.